Kompetensi Guru Pengampu Minat Kreatif Bidang Musik Di SLB Yayasan Mitra Ananda Padang - Anggur Pratama; Agung Dwi Putra (FBS Universitas Negeri Padang, 2022)
This study aims to determine the competence of music teachers who teach at SLB Mitra Ananda Padang Foundation. This type of research is qualitative research with a descriptive approach. The object of this research is a teacher who teaches music subjects at the SLB Mitra Ananda Foundation. Data collection techniques were carried out employing observation, interviews, documentation and literature study. The types of data used are primary and secondary data. Data analysis techniques are carried out by categorizing field data sources, bringing up findings from each field data category, bringing up the categorization of findings, and discussing findings with the theoretical basis used. Based on the results of the research that has been carried out, it can be concluded that the teachers of creative interest in music at the SLB Mitra Ananda Padang Foundation have achieved the expected learning competencies. this is because the teacher has general competence and received a reference book from the principal of the SLB Foundation Mitra Ananda Padang, as a reference and guide for teaching children with special needs.